2012
DOI: 10.1088/0963-0252/21/3/034008
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in atmospheric-pressure plasma jets

Abstract: Abstract:We report detailed characterization of a low-temperature atmosphericpressure plasma jet that exhibits regimes of periodic, quasi-periodic and chaotic behaviors. Power spectra, phase portraits, stroboscopic section and bifurcation diagram of the discharge current combine to comprehensively demonstrate the existence of chaos, and this evidence is strengthened with a nonlinear dynamics analysis using two control parameters that maps out periodic, period-multiplication, and chaotic regimes over a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…electron cited from [25] and i  is its mean energy; σs represents the surface charge density on the wall, and Je and Ji respectively denote the electron density and the ion density there; D1 and D2 are the electric displacement vectors on both sides of the interface; αs is a switching function as given below. (12) Here, q represents the signed charge. For chemical kinetics, we reused ones from our previous work [19].…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…electron cited from [25] and i  is its mean energy; σs represents the surface charge density on the wall, and Je and Ji respectively denote the electron density and the ion density there; D1 and D2 are the electric displacement vectors on both sides of the interface; αs is a switching function as given below. (12) Here, q represents the signed charge. For chemical kinetics, we reused ones from our previous work [19].…”
Section: Model Descriptionmentioning
confidence: 99%
“…However, under certain conditions, a lot of simulation and experimental research has reported that DBDs can also work in various nonlinear modes such as asymmetric period-one (henceforth called AP1), multi-period, quasi-period and chaos through different evolution routes [8][9][10][11]. Since different discharge modes can influence the stability of DBDs in terms of the density and composition of active species in discharge plasmas and then impact their efficacy in related applications [12,13], the investigation on the control of nonlinear modes is valuable and imperative both in theoretical and practical aspects. It is worth noting that before bifurcating into other nonlinear modes from SP1, the discharge always first transforms into the asymmetric mode as a transition phase [14].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, in each position, the current amplitudes fluctuate stochastically with time, which is identical with the temporal chaos observed previously. [4][5][6][7][8] Taking the five-channels pattern for example, we study the formation process of pattern. Figures 11 and 12 present the temporal evolutions of electron density and surface charge density along y-direction including 30 periods.…”
Section: -2mentioning
confidence: 99%
“…31. The calculated u h and u l are substituted into the boundary condition (8) and (9). Using the above boundary conditions of Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Recently, more complex temporal nonlinear behaviors of APGD, such as period-doubling bifurcation and chaos, have been frequently observed in both experiments and numerical simulations. [13][14][15][16][17][18][19] Different from the single period discharge, the current pulses in period-doubling and chaos discharges repeat at multiple applied voltage cycles or fluctuate stochastically. These nonlinear behaviors are sensitive to discharge parameters and can be caused by the fluctuations of a variety of control parameters, such as the driving frequency, voltage amplitude, and gap width.…”
Section: Introductionmentioning
confidence: 99%